Single versus multi-dose intra-articular injection of platelet rich plasma in early stages of osteoarthritis of the knee: A single-blind, randomized, superiority trial - Koushik Subramanyam; Rajkumar Alguvelly; Abhishek Mundargi; Prakash Khanchandani (Archives of Rheumatology, 2021)
Objectives: This study aims to compare the effectiveness of single, double, and triple doses of intra-articular (IA) platelet rich plasma (PRP) in early stages of osteoarthritis (OA) of the knee. Patients and methods: This single-blind, randomized, superiority trial included a total of 180 knees of 90 patients (22 males, 68 females; mean age: 47.9 years; range, 36 to 60 years) with bilateral OA knee of Kellgren-Lawrence Grade 1-2 between May 2017 and December 2018. The patients were randomized (30 in each group) to receive single, double, or triple doses of IA PRP (two weeks apart in repeat injections). The outcome measures were Visual Analog Scale, International Knee Documentation Committee Score, Knee Injury and Osteoarthritis Outcome Score, and Tegner Lysholm Knee Score. The assessor of outcome was blinded. The scores were collected before intervention and at six weeks, three months, six months, and one year after the intervention. Results: All patients completed the study. All three groups were comparable with respect to demographic and disease characteristics. All four scores were comparable among the three groups before intervention and at six weeks, three months, and six months. However, at one-year follow-up, the three-dose group showed superiority to others in terms of all four scores. All three groups showed improvement until six months and deterioration thereafter, which was only marginal in the three-dose group. All groups showed a statistically significant improvement of scores compared to baseline scores at one year. There were no major complications. Conclusion: The IA administration of three doses of PRP yields superior outcome to single and double doses at the end of one year. Repeat doses are probably needed to sustain the benefit achieved at one year.